Living in the mountains: Mobilities, forms of residentiality and local identities of new inhabitants of a Swiss ski resort - Andrea Friedli (Via@)
The tendencies of the revalorisation of rural spaces and subsequent rural gentrification have been studied under the notion of “amenity migration” in different geographic contexts. The new dwellers keep their social networks in the cities and import their urban lifestyles to their new homes. This contribution focuses on the (re)negotiation of the local identities and “local knowledge” in Verbier, a ski resort in the Swiss Alps. Verbier grew from a small mountain hamlet to a pulsating resort for ski tourists over the last 50 years, and currently, new residents and people practicing multilocal residentiality reshape the local communities and representations of the locality.